Study of the Mechanical Properties for Reed -Reinforced Epoxy Composites and Reed-Sisal Hybrid Epoxy Composites - Mokhilif, Mohammed .H (University of Thi-Qar Journal of Science, 2014)
In this investigation, the mechanical properties such as : elongation, tensile strength, flexural strength and impact properties were studied for epoxy composites reinforced with reed in weight percentages of (0,15,25 and 35)% and epoxy composites reinforced with reed-sisal in weight percentages (5,10 and 15)%.Hand-lay up was used to prepare the composites ,sisal fibers and reed fibers were treated with NaOH .The results showed that the tensile strength , flexural strength and impact increase with the increase in weight percentages of reed and decrease in elongation with increase of the loading, the hybrid composites showed an increase in tensile and impact properties with increase in weight percentages of fibers and decrease in elongation with increase in the reed loading and increase in flexural strength with increase in sisal fibers loading.